Constitutional Environmental Rights: Investigating their Potentials for a Sustainable Niger Delta - Odong, Nsikan-Abasi Umana (Université d'Ottawa / University of Ottawa, 2023)
Nigeria is at a crossroad - how to balance developmental needs with environmental protection. The challenge is exacerbated because Nigeria operates a mono-economy which overwhelmingly depends on the crude oil resources from the Niger Delta for its economic survival. As a result, the protection of the Niger Delta environment has not been accorded the priority it deserves. The thesis aims to investigate the potentials of Constitutional Environmental Rights (CERs) to assist in resolving the environmental sustainability crisis in the Niger Delta. The thesis will utilize insights developed by environmental justice scholarship as the theoretical framework to investigate the main causes of the sustainability crisis in the Niger Delta and to propose ways to tackle these environmental challenges. The thesis draws inspiration from the research carried out by David Boyd on the efficacy of CERs for environmental sustainability for its analytical framework. Although Trans-National Corporations (TNCs) and international trade contribute to the sustainability crisis in the Niger Delta, the thesis will not focus on these. Instead, it will focus on the internal legal causes of the sustainability crisis in the Niger Delta, because the external causes of the sustainability crisis have been addressed at length by other researchers. Moreover, addressing the internal causes of the sustainability crisis could also address some of the impacts of the external causes of the sustainability crisis in the Niger Delta. As such, the thesis uses 3 of Boyd's CERs performance indices in analyzing the suitability of CERs to tackle the 3 identified major internal causes of the sustainability crisis in the Niger Delta. Specifically, Boyd's index 1 (impetus for the enactment of stronger environmental laws) could address gaps in Nigeria's environmental regulatory framework. Index 4 (improvement in the implementation and enforcement of environmental laws) could address the non-implementation and non-enforcement problems with the existing environmental regulatory framework in Nigeria. Lastly, index 6 (increased public participation in environmental governance) could address the marginalization of the Niger Delta in resource governance in Nigeria. These indices will not only help to uncover the weaknesses in Nigerian laws and their enforcement but will also identify potential barriers to CERs within the current legal and policy architecture and suggest solutions on how CERs would be implemented if recognized in Nigeria to avoid these barriers. The main contribution of the thesis is a detailed case study of how CERs may work in Nigeria to tackle the environmental crisis in the Niger Delta, and a detailed and specific analysis of what would be required in terms of domestic political, structural and legal change to ensure that CERs could contribute to the sustainability of the Niger Delta as much as they have in other countries. The research makes specific recommendations for changes to Nigerian law, policy and institutions, such as adoption of CERs in the enforceable part of the Constitution, ownership and control by federating units of natural resources found in their territories, and elimination of barriers to access to justice. This would come about through strategically crafted constitutional provisions and laws to address the underlying factors that would limit the effectiveness of CERs in Nigeria. The thesis argues that addressing these fundamentals and constitutionalizing environmental rights will lead to improved environmental outcomes for the Niger Delta.
Keywords: Environment; Sustainability; Constitutional Environmental Rights; Niger Delta; Environmental Justice; Access to Justice